Multiple primary malignancies: a report of two cases - Sakellakis, Minas; Peroukides, Stavros; Iconomou, Gregoris; Boumpoucheropoulos, Sotirios; Kalofonos, Haralabos (Chinese Journal of Cancer Research; Vol 26, No 2 (April 26, 2014): Chinese Journal of Cancer Research, 2014)
The diagnosis of multiple primary malignancies (MPMs) in a patient has been reported rather frequently during the past decade. Here we present two cases with three synchronous primary malignant tumors. The first patient is a 66-year-old male with synchronous colorectal cancer, renal cell carcinoma (RCC) and non-small cell lung cancer (NSCLC). The second patient is a 64-year-old female with breast cancer, transitional cell carcinoma of the ureter and endometrial cancer. MPMs seem to be diagnosed in a higher incidence than that predicted only by the influence of hazard and, whenever found, they raise questions regarding not only possible common etiologic factors or same pathogenetic mechanisms but also they cause a lot of troubles to both clinicians and patients because the therapeutic options usually become limited.